Negotiating Risk and Promoting Empowerment through Rap Music: Development of a Measure to Capture Risk and Empowerment Pathways to Change. - Travis, Raphael; Bowman, Scott Wm. (Journal of Human Behavior in the Social Environment)
The purpose of this study was to report on the development and construction of the Individual and Community Empowerment (ICE) inventory, a measure seeking to capture the specific pathways by which either risk-enhancing impacts or empowering impacts of rap music manifest. Data were analyzed via structural equation modeling from a convenience sample of 128 high school and college students. Results found that respondents elicited (1) empowering themes that related to them individually and to the broader community and (2) high-risk themes that may promote risky health behaviors. Implications about research and practice relevance of the ICE inventory are discussed.